1997
DOI: 10.1086/303561
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Flow in Nova Outbursts

Abstract: Thermonuclear burning in hydrogen envelopes is studied using two-dimensional simulations, in a broader manner than that presented recently by Glasner & Livne. The evolution of the convective burning process before and during thermonuclear runaway (TNR) is discussed. We study the coupling between the burning and the hydrodynamics, which determines the nature of the convective Ñow, and analyze the relevant timescales. The consequences of the combustion and the nucleosynthesis are investigated in detail. The comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
144
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(159 citation statements)
references
References 39 publications
13
144
2
Order By: Relevance
“…The onset of the instabilities in such an extremely low numerical diffusion regime is substantially delayed. The simulations reported by Glasner et al (1997) A similar behavior is also found for the time required for the convective front to reach the outer boundary, t Y , and for the history of the nuclear energy generation rate (Fig. 4).…”
Section: Effect Of the Grid Resolutionsupporting
confidence: 74%
See 1 more Smart Citation
“…The onset of the instabilities in such an extremely low numerical diffusion regime is substantially delayed. The simulations reported by Glasner et al (1997) A similar behavior is also found for the time required for the convective front to reach the outer boundary, t Y , and for the history of the nuclear energy generation rate (Fig. 4).…”
Section: Effect Of the Grid Resolutionsupporting
confidence: 74%
“…As in Casanova et al (2010), we used the same initial model as Glasner et al (1997) and Kercek et al (1998): a 1 M CO white dwarf that accretes solar composition matter (Z = 0.02) at a rate of 5 × 10 −9 M yr −1 . The model was evolved spherically (1-D) and mapped onto a 2-D cartesian grid, when the temperature at the base of the envelope reached ≈10 8 K. It initially comprised 112 radial layers -including the outermost part of the CO core -and 512 horizontal layers.…”
Section: Input Physics and Initial Conditionsmentioning
confidence: 99%
“…The free outflow (open) boundary condition used in Eulerian schemes artificially quenches the runaway. Use of such a boundary condition in Eulerian simulations can explain the main differences between the models presented by Glasner et al (1997) and those of Kercek et al (1998). The fact that in the latter simulation virtually all of the hydrogen disappears from the grid at late times ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The few multidimensional models of mixing at the coreenvelope interface available to date have proven particularly controversial. Indeed, two independent, two-dimensional studies (Glasner et al 1997;Kercek et al 1998), based upon the same 1-D initial model, reached totally different conclusions about the strength of the runaway and its capability to power a fast nova. The origin of such differences was carefully analyzed by Glasner et al (2005), who concluded that the early stages of the explosion, prior to the onset of the TNR -when the evolution is almost quasi-staticare extremely sensitive to the outer boundary conditions.…”
Section: Multidimensional Nova Models: the Next Frontiermentioning
confidence: 99%